Reduced heart rate variability is associated with disease severity in AL amyloidosis: a retrospective cohort study - Xiao-hang Pei; Su-qiong Zuo; Pan Zhou; Rong-jun Ma; Zun-min Zhu; Xiao-li Yuan (Frontiers in Medicine, 2026)
Background Autonomic nervous system involvement is common in systemic amyloidosis, yet the clinical relevance of heart rate variability (HRV) in immunoglobulin light-chain (AL) amyloidosis remains incompletely defined. Methods In this retrospective cohort study, 56 patients with biopsy-proven AL amyloidosis and 33 age- and sex-comparable healthy controls underwent 24 h Holter monitoring. Time- and frequency-domain HRV parameters were recorded. Associations of HRV with cardiac involvement assessed by cardiac magnetic resonance (CMR), Mayo 2004 stage, and short-term treatment response were evaluated using group comparisons and multivariable regression. Results Compared with controls, patients with AL amyloidosis had significantly higher mean heart rate and lower SDNN, total power (TP), and all frequency-domain components (ULF, VLF, LF, and HF) (all P < 0.05). Patients with CMR-defined cardiac involvement showed a higher prevalence of HRV abnormalities and lower SDNN, SDANN, pNN50, TP, ULF, VLF, and LF than CMR-negative patients (all nominal P < 0.05). In multivariable models, troponin remained independently associated with CMR-positive status, whereas HRV indices did not retain independent significance. By Mayo 2004 stage (I/II/III: 11/20/25), SDANN and VLF declined progressively with advancing stage ( P < 0.05), and SDANN remained independently associated with higher stage after adjustment for troponin. In the exploratory subset with paired follow-up Holter recordings ( n = 33), most HRV parameters did not change significantly after therapy; however, the coefficient of variation (CV) showed a statistically significant increase following treatment ( P = 0.037). Conclusion Reduced HRV is a prominent feature of AL amyloidosis and is independently associated with Mayo stage after adjustment for cardiac biomarkers. These findings position HRV as a non-invasive marker of autonomic involvement that complements established cardiac biomarkers in characterising disease severity in AL amyloidosis; whether this translates into independent prognostic value requires evaluation in prospective outcome studies.